Different Forms of Tumor Vascularization and Their Clinical Implications Focusing on Vessel Co-option in Colorectal Cancer Liver Metastases - Haas, Gwendolyn; Fan, Shuang; Ghadimi, Michael; De Oliveira, Tiago; Conradi, Lena-Christin (Frontiers in Cell and Developmental Biology, 2021)
In modern anti-cancer therapy of unresectable colorectal cancer liver metastases (CRCLM) the anti-angiogenic treatment targeting sprouting angiogenesis is firmly established for more than a decade. However, its clinical benefits still remain limited. One reason for these limitations consist in an alternative way of blood supply known as vessel co-option (VCO), which differs fundamentally from the well-known sprouting angiogenesis. Vessel co-option is observed in a significant fraction of CRCLM. In this scenario tumor cells hijack pre-existing mature vessels of the host organ independently from generating new vessels. This represents an escape mechanism from the common anti-angiogenic anti-cancer treatments, as they primarily target the main trigger of sprouting angiogenesis, the vascular endothelial growth factor alpha. Moreover, the mechanism of blood supply in CRCLM can be simply deduced from their phenotypic histopathological growth patterns (HGP). For that, a specific guideline has already been implemented. These HGP vary not only regarding their blood supply, but also concerning their tumor microenvironment (TME), as notable differences in immune cells infiltration and desmoplastic reaction surrounding the CRCLM can be observed. The latter actually serves as one of the central criteria for the classification of the HGP. Regarding the clinically relevant effects of the HGP, it is still a topic of research whether the VCO-subgroup of CRCLM results in an impaired treatment response to anti-angiogenic treatment when compared to an angiogenic subgroup. However, it is well proved, that VCO in CRCLM generally relates to an inferior survival compared to the angiogenic subgroup. Altogether the different types of blood supply result in a relevant influence on the patients’ prognosis. This reinforces the need of an extended understanding of the underlying mechanisms of VCO in CRCLM with the aim to generate more comprehensive approaches which can target tumor vessels or even components of the TME. This review aims to augment the current state of knowledge on VCO in CRCLM and other tumor entities and its impact on anti-angiogenic anti-cancer therapy.